Challenging Stigma: The Performative Strategies of Janger Artists in Banyuwangi - Dear Lova Sukoco; Rosnida Sari (Pusat Studi Gender Universitas Jember, 2025)
This study focuses on the dynamics of self-image among female artists in the traditional Janger performance group, Sri Budoyo Pangestu (SBP), Banyuwangi, using Erving Goffman's dramaturgical approach. The main objective of the research is to explore how women as Janger performers overcome the social stigma attached to their profession. The study employs a qualitative method with a phenomenological approach. The findings reveal that the negative stigma toward female Janger artists—particularly the stereotypes of being